Feasibility study of gasification of oil palm fronds - Sulaiman, S.A. (Universiti Malaysia Pahang, 2015)
Considering the large and consistent supply, oil palm fronds could be a promising source of biomass energy through gasification. There is very scarce information on the characteristics of oil palm fronds, which is vital in deciding if such biomass is technically suitable for gasification. In the present work, the feasibility of oil palm fronds for biomass gasification is studied. The study is conducted experimentally via standard tests to determine their thermochemical characteristics. Ultimate analysis is conducted to determine the contents of carbon, nitrogen, hydrogen and sulphide in oil palm fronds. Proximate analysis is performed to identify the burning characteristics of the biomass. The energy content in the fronds is determined by using a bomb calorie meter and is around 18 MJ/kg. The ignitability of the fronds is also studied experimentally to assess the ease to start-up combustion of the fronds. The characteristics of the flame of the resulting syngas from gasification of oil palm fronds are qualitatively studied. Simulated syngas composition study reveals potentials of 22 CO, 1.3 H2, 18.5 CO2 and traces of CH4. The study is extended to computer simulation to predict composition of the syngas. It is found from this work that oil palm fronds are feasible for gasification and has a good potential as a renewable energy source. Â© 2015 Universiti Malaysia Pahang, Malaysia.